Ultrasound-guided fine needle aspiration of thyroid nodules: factors affecting diagnostic outcomes and confounding variables. (March 2017) - Kavanagh, John; McVeigh, Niall; McCarthy, Eoghan; Bennett, Kathleen; Beddy, Peter
Background: The incidence of thyroid cancer is increasing in men and women. Fine needle aspiration (FNA) is an accepted technique to assess thyroid nodules but is associated with a high rate of non-diagnostic sampling. Purpose: To assess the diagnostic performance of ultrasound-guided FNA of thyroid nodules and identify factors associated with non-diagnostic sampling. Material and Methods: A retrospective review of thyroid FNAs was performed between 2006 and 2013. Patient demographics, nodule characteristics, procedural technique, cytology, and complications were recorded. Cytology was categorized THY1-5 based on the British Thyroid Association guidelines. Descriptive and multivariable analysis were conducted to identify factors associated with non-diagnostic sampling. Results: A total of 724 procedures were identified with 597 (82.5%) in women, and an overall mean age of 40 years (age range, 17–87 years). Factors associated with a non-diagnostic outcome in the multivariable regression analysis included increasing lesion depth (OR, 1.05 per mm; 95% confidence interval [CI], 1.007–1.10), age (OR, 1.012 per year; 95% CI, 1.0–1.025) and number of FNA passes (1 vs. 4+; OR, 6.07; 95% CI, 2.27–16.21). The complication rate was 1.1% related to perilesional hematomas and vaso-vagal episodes. Conclusion: Thyroid FNA is a safe and reliable procedure for cytological assessment of thyroid nodules. Deeper nodules and older patients are more likely to have non-diagnostic samples.